Extraction of collagen from catfish (Clarias gariepnus) waste and determination of its physico-chemical properties / Normah Ismail and Nurul Asyiraf Abdul Jabar - Ismail, Normah; Abdul Jabar, Nurul Asyiraf (Research Management Institute, 2012)
Collagen was extractedfrom catfish (Clarias gariepnus) waste using 0.5M acetic acid and its subsequent precipitation in 2.6M NaCI. The resultant collagen was analysed with respect to its moisture content and physicochemicalproperties including yield, pH, protein content, colour, odour and thermal stability. Ayieldof16.4% andpositive collagen attributes indicate that catfish waste has potential as a collagen source. The snowy white, crystal-like and light textured collagen comprises of5.97% protein and 0.46% moisture, and exhibits a pH of4.75. Sensory evaluation indicates that the collagen has a slight fishy odour. Viscosity analysis indicates a steady decrease with increasing temperature over the range considered (20-50°C). The pale colour exhibited and limited odour emitted by the extracted collagen indicate that catfish waste collagen could be applied in the food industry without resulting in any undesirable food products attributes. Differential Scanning Calorimetry (DSC) analysis indicated that the collagen exhibits good thermal stability and denatures at a high temperature in a similar manner to mammalian collagen